Addressing Imbalances in US Nuclear Economic and Nonproliferation Policies - Matthew S Duchene; Howard L. Hall (International Journal of Nuclear Security, 2015)
Foreign civilian nuclear start-ups have an increasing number of international partners capable of supplying fuel cycle technologies. The desire to prevent the spread of dual-use enrichment and reprocessing technology by asking partner states to rely on international fuel markets is a major obstacle for US negotiating civilian nuclear trade agreements, leading to delays. US participation in emerging nuclear markets is being undercut by foreign competition, leading to decreasing economic competition and influence in international nonproliferation issues. It is therefore necessary for the US to reinvest and complete its domestic nuclear fuel cycle and modify its process for implementing civilian nuclear cooperation agreements with other states. By reducing delays in negotiations, having a larger stake in the uranium fuel supply provided to international markets, and outlining a clear waste policy, Washington will advance both its economic and nonproliferation goals.
Keywords: U.S. Nuclear Policy; Nuclear Fuel Cycle; Nuclear Trade; Nonproliferation